Gamma-irradiation effect on kinetic parameters of glass-ceramic materials - Selçuk, AB; Yavuz, H (Elsevier Science Bv, 2003)
Non-isothermal crystallization process in glass composition 33% CuO-67% PbO before and after gamma irradiation has been investigated using differential scanning calorimetry (DSC). The samples have been irradiated with the dose of 50 Mrad and with the gamma-sources Co-60. DSC measurements were taken for different heating rates. Kinetics parameters were determined for different heat treatment applied samples by using Johnson-Mehl-Avrami-Kolmogorov (JMAK) equations. The computed values of kinetics parameters of samples before and after gamma irradiation have also compared. The values of peak crystallization temperature, activation energy and Avrami exponent have been decreased for irradiated samples. (C) 2003 Elsevier Science B.V. All rights reserved.
Keywords: crystallization kinetics; activation energy; gamma irradiation; glass-ceramics